Benchmarking stability of bipedal locomotion based on individual full body dynamics and foot placement strategies - application to impaired and unimpaired walking - Ho Hoang, Khai-Long; Wolf, Sebastian Immanuel; Mombaur, Katja (Frontiers in robotics and AI, 2018)
The principles underlying smooth and effortless human walking while maintaining stability as well as the ability to quickly respond to unexpected perturbations result from a plethora of well-balanced parameters, most of them yet to be determined. In this paper, we investigate criteria that may be useful for benchmarking stability properties of human walking. We perform dynamic reconstructions of human walking motions of unimpaired subjects and subjects walking with transfemoral prostheses from motion capture recordings using optimal control. We aim at revealing subject-specific strategies in applying dynamics in order to maintain steady gait considering irregularities such as deviating gait patterns or asymmetric body segment properties. We identify foot placement with respect to the Instantaneous Capture Point as the strategy globally applied by the subjects to obtain steady gait and propose the Residual Orbital Energy as a measure allowing for benchmarking human-like gait towards confident versus cautious gait.
Gesehen am 15.10.2018